Narrative Construction between the Arabic and Chinese Novel: Naguib Mahfouz and Ba Jin as two examples - Khataybeh, Yousef Saleh (Dirasat: Human and Social Sciences, 2024)
Objectives: This study aimed to clarify the connections and the relationships between the Arabic novel and the Chinese novel. It also intended to show the novelistic artistry in the trilogies of Naguib Mahfouz and Ba Jin and compares the ways through which they address tradition, life, and society- especially family life-in their trilogies. Methods: The research attempted to answer the following questions: What are the connections and relationships between Arabic and Chinese literatures? How can studying the two trilogies by Naguib Mahfouz and Ba Jin help study the two literary traditions? The researcher employed the comparative in addition to the analytical-descriptive approaches to reach accurate results about the two trilogies through examining the narrative structures of the two works and the topics that they address. Results: This study uncovered the intellectual and artistic components in the works of each of them and showed the relationship between Chinese and Arabic literature. Additionally, it pointed to the daily living realities, be it in Egypt or China. The study concluded that Naguib Mahfouz and Ba Jin are similar in their narrative structure and that the two writers expressed their perspectives on tradition as well as the social and economic circumstances of their respective societies, shedding light on the effect of colonization on the two countries. Conclusions: Both writers, each advocating for their respective countries and causes, produced literary works that gained psychological interest due to their experiences under colonialism. Additionally, both explored the clash between ancient and contemporary values in their writings.